Design of slender reinforced concrete column using Indian design code and Chinese design code (dual project) - Shi, Wan Lei (2015)
Column is one of the essential structural elements in a building. With the rising popularity in space utilization, the use of slender column receives increasing demand. The objective of the project is on the study of slender concrete columns under short-term loading and uniaxial bending with eccentricities at the ends. The core of the report will be placed on the evaluation of the Chinese design code GB50010-2010, particularly on the design approach for slender reinforced concrete column. To facilitate the study, Eurocode 2 was introduced for comparison. Extensive analysis and comparisons of 152 column data with eccentricity to depth ratio e/h from 0 to 0.75, length to depth ratio L/h from 15 to 50, percentage of reinforcement Ast/bh from 0.89 to 5.24, concrete strength from 16.7N/mm2 to 106.7N/mm2, steel strength from 206N/mm2 to 625N/mm2 were conducted in the study presented in the report. Data analysis results reveal the trends that the increase in the e/h ratio or L/h ratio while keeping the other parameters constant will reduce the column load carrying capacity, and the effect is more significant when these two ratios are relatively low; the use of the higher concrete strength and higher reinforcement percentage may increase the column load carrying capacity, however, excessive reinforcement may inversely affect the strength of the columns due to the interference of the bonding mechanism between concrete and reinforcement. In general, it is observed from the analysis results that GB50010-2010 is less conservative than the Eurocode 2 for slender column design. In addition, GB50010-2010 is found to be unsafe for slender columns subjected to high e/h ratio, or high L/h ratio; while on the other hand, it is concluded to be over conservative for columns with initial eccentricity less than the minimum eccentricity provision stated in the code. To overcome the shortcomings in the design, alternative design modifications have been proposed to improve the design under certain conditions and verification work have been conducted before conclusions are drawn. With the increased popularity in the use of slender columns in the modern buildings, it is encouraged to put more research efforts for a more comprehensive and holistic slender concrete column design development.